Shampoo Bar (SHABAR) SHABAR : Shampoo Bar from Moringa Leaves - Muhammad Rizqy Zamzami Al-fateeh; Axl Banyu Satria; Abdullah Umair; Akma Radithya Ukail; Gabriel Ahza Albadra; Vany Destiany (GLOBAL SCIENTS PUBLISHER, 2026)
The growing consumer demand for natural and environmentally friendly hair care products reflects increased awareness of the negative impacts of synthetic chemicals and plastic pollution. This study aims to formulate and evaluate a shampoo bar based on Moringa oleifera leaf extract as an alternative to conventional liquid shampoos. The formulation was carried out using the cold saponification method with coconut oil, olive oil, and castor oil as the main base oils, and natural essential oils such as lavender and tea tree as fragrance and antimicrobial agents. Moringa leaf extract was added during the cooling phase to preserve the stability of its bioactive compounds, which are known to help prevent hair loss. The results showed that the formulated shampoo bar had a safe pH level (5.5–6.5), did not cause irritation after 24–48 hours of use, and received positive responses in organoleptic testing. Of the 25 respondents, 64% liked the product and 12% reported high satisfaction. The natural green color and fresh scent of moringa combined harmoniously with the essential oils, enhancing the product's sensory appeal. With the presence of flavonoids, saponins, and alkaloids, this shampoo bar is not only safe to use but also has potential benefits in reducing hair loss naturally. Moreover, its solid form supports sustainability by reducing the use of single-use plastic packaging.